2016
DOI: 10.1037/ccp0000056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relationship education on couple communication and satisfaction: A randomized controlled trial with low-income couples.

Abstract: Relationship education programs produce small improvements in relationship satisfaction and communication, particularly for couples at elevated sociodemographic risk. The absence of behavioral effects on satisfaction indicates, however, that the mechanisms by which couples may benefit from relationship education are not yet well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
5
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 32 publications
4
94
5
5
Order By: Relevance
“…A number of scholars over the past decade have explored whether CRE can be effective for more disadvantaged and distressed couples. The early evidence here is mixed, with some rigorous studies finding no effects (Wood, Moore, Clarkwest, & Killewald, ), others finding small positive effects (Amato, ; P. A. Cowan, Cowan, Pruett, Pruett, & Wong, ; Williamson, Altman, Hsueh, & Bradbury, ), and still others finding larger positive effects (Cox & Shirer, ; Stanley et al, ). See Hawkins and Erickson () for a meta‐analytic summary of this early research.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…A number of scholars over the past decade have explored whether CRE can be effective for more disadvantaged and distressed couples. The early evidence here is mixed, with some rigorous studies finding no effects (Wood, Moore, Clarkwest, & Killewald, ), others finding small positive effects (Amato, ; P. A. Cowan, Cowan, Pruett, Pruett, & Wong, ; Williamson, Altman, Hsueh, & Bradbury, ), and still others finding larger positive effects (Cox & Shirer, ; Stanley et al, ). See Hawkins and Erickson () for a meta‐analytic summary of this early research.…”
mentioning
confidence: 82%
“…However, FE couples were 20% more likely to be continuously together at the 3‐year follow‐up assessment compared with control‐group couples. In the Supporting Healthy Marriage study (Williamson et al, ), low‐income married couples in the Oklahoma City treatment group showed a pattern of small but statistically positive gains compared with control couples at the short‐term and the 30‐month assessments. The present study of FE draws from ongoing evaluation efforts, but those efforts no longer include a control group.…”
Section: Methodsmentioning
confidence: 99%
“…For RE programs, a meta-analysis of low-income couples found participants with longer relationship length improved marginally more than couples with shorter relationship length. Additionally, an investigation into couples in the Supporting Healthy Marriage Project found that pre-treatment sociodemographic risk, operationally defined as less education, unemployment, or receiving public assistance among other indicators, did not predict gains in relationship satisfaction at 30 months (Williamson, Altman, Hsueh, & Bradbury, 2016). A second study found that risk did predict satisfaction over follow-up such that high risk couples declined at a slower rate than low risk couples (Williamson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Men and women reported lower psychological abuse at 12 months, and women continued to report lower psychological abuse at 30 months (Hsueh et al, ; Lundquist et al, ). In a 12‐month follow‐up observational study, SHM couples were observed to have better communication skills, and women were observed to have lower anger and hostility than women in the control group (Hsueh et al, ; Williamson, Altman, Hsueh, & Bradbury, ). Notably, there were no statistically significant impacts of SHM on relationship dissolution.…”
Section: Introductionmentioning
confidence: 99%